2014
DOI: 10.1021/om500349s
|View full text |Cite
|
Sign up to set email alerts
|

Apicophilicity versus Hydrogen Bonding. Intramolecular Coordination and Hydrogen Bonds in N-[(Hydroxydimethylsilyl)methyl]-N,N′-propyleneurea and Its Hydrochloride. DFT and FT-IR Study and QTAIM and NBO Analysis

Abstract: Conformers of N-[(hydroxydimethylsilyl)methyl]-N,N′-propyleneurea (1) and their hydrochlorides (2) with HCl coordinated to different basic sites have been studied experimentally by FT-IR and theoretically using the density functional theory (DFT) method at the B3LYP/6-311+G(d,p) and M06/6-311+G(d,p) levels of theory. The structures of silanols 1 and 2 are determined by the balance of two competing effects: namely, intramolecular CO→Si coordination and intramolecular C OThe preferred conformation of silanol 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…The calculated topological parameters of the BCPs and calculated QTAIM energies of intramolecular coordination and intermolecular hydrogen bonds have shown that the C=O→Si bonds are relatively strong and contain covalent contribution, whereas weak hydrogen bonds are electrostatic in nature. This is their distinction from silanols, in which the energy of the C=O→Si intramolecular coordination bonds and of hydrogen bonds C=O···HO may be comparable and dependent both on the axial substituent at silicon and the center of basicity in the molecule to which the HCl molecule is coordinated . The energy of the C=O→Si bond in H‐complexes of conformer 1a exponentially depends on the interatomic distance O→Si.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The calculated topological parameters of the BCPs and calculated QTAIM energies of intramolecular coordination and intermolecular hydrogen bonds have shown that the C=O→Si bonds are relatively strong and contain covalent contribution, whereas weak hydrogen bonds are electrostatic in nature. This is their distinction from silanols, in which the energy of the C=O→Si intramolecular coordination bonds and of hydrogen bonds C=O···HO may be comparable and dependent both on the axial substituent at silicon and the center of basicity in the molecule to which the HCl molecule is coordinated . The energy of the C=O→Si bond in H‐complexes of conformer 1a exponentially depends on the interatomic distance O→Si.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we have shown that N ‐[hydroxy(dimethyl)silylmethyl]‐ N,N′ ‐propylene urea can form two types of intramolecular bonds: coordination bond C=O→Si and hydrogen bond C=O···H–O. In its hydrochloride, the strength of the C=O→Si bond depends on to which center of basicity in the molecule is the molecule of HCl bound . In continuation of this study we present here the results of experimental and theoretical investigation of the interaction of (acyloxymethyl)trifluorosilanes RC(O)OCH 2 SiF 3 having the intramolecular coordination bond C=O→Si–F, with proton donors.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…11,12,[53][54][55][56] The significance of the chemical or physical interactions between MET and radical species can be assessed by using the total sum of the delocalization energies, ΣE (2), obtained by summing the electron delocalization energies of all the significant interactions between the NBO orbitals of interacting molecules. 57,58 The ΣE (2) values are reported in Table 3.…”
Section: Natural Bond Order (Nbo) Analysismentioning
confidence: 99%
“…9 Additional oxidants, such as H 2 O 2 , By employing computer simulations within the framework of the density functional theory (DFT), it is possible to gain insight into the changes of the investigated structures as a consequence of the presence of other molecules in the system. 11,12 The information thus obtained is very important to further understand the degradation mechanisms of the investigated compounds. 13,14 Fukui functions and Fukui indices are often used as local quantum-molecular descriptors.…”
Section: Introductionmentioning
confidence: 99%